The Healing past : pharmaceuticals in the biblical and rabbinic world - Jacob, Irene, 1928-; Jacob, Walter, 1930- (Studies in Ancient Medicine, 1993)
This volume focuses on our present knowledge of pharmaceuticals in the Biblical and Rabbinic world, a subject which has received little attention. Although many aspects of ancient Near Eastern cultural life have been studied thoroughly, no one has dealt with the pharmaceutical knowledge of this period. The essays in this study deal with their themes in different ways. They thus provide the best current information on a particular subject. They also demonstrate various approaches which may prove fruitful for further investigation. References in specialized studies and archeological field work have demonstrated that our knowledge in this area continues to grow. The fragmented and isolated nature of this material has led to it remaining unknown to those interested in the history of medicine, pharmacy, and horticulture. The authors have sought to fill this gap.